1991
DOI: 10.1172/jci115419
|View full text |Cite
|
Sign up to set email alerts
|

Use of an anti-low density lipoprotein receptor antibody to quantify the role of the LDL receptor in the removal of chylomicron remnants in the mouse in vivo.

Abstract: Lipoproteins are removed from the plasma by LDL receptordependent and -independent pathways. The relative contribution of these has been established for LDL by using modified lipoproteins, but this has not been possible for apoE-rich lipoproteins, such as chylomicron remnants. To do this, we used a monospecific antibody to the rat LDL receptor. The antibody was injected intravenously into mice followed by '25I-lipoproteins. Blood samples were obtained sequentially and radioactivity measured to determine the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 45 publications
5
55
0
Order By: Relevance
“…Supporting this, it was reported that clearance ofchylomicron remnants in LDL receptor deficiency is normal in the retinyl palmitate-loading test on the patients with familial hypercholesterolemia (39). Meanwhile, it was reported that the LDL receptor plays a large role in the clearance of chylomicron remnants in rats from study of the effect of injection of anti-LDL receptor antibody (40).…”
Section: Discussionmentioning
confidence: 84%
“…Supporting this, it was reported that clearance ofchylomicron remnants in LDL receptor deficiency is normal in the retinyl palmitate-loading test on the patients with familial hypercholesterolemia (39). Meanwhile, it was reported that the LDL receptor plays a large role in the clearance of chylomicron remnants in rats from study of the effect of injection of anti-LDL receptor antibody (40).…”
Section: Discussionmentioning
confidence: 84%
“…In transgenic animals, nearly all of this enhanced uptake occurred in the liver, consistent with earlier investigations that demonstrated chylomicrons with excess apo E are cleared preferentially by the liver (41, 43, 50). The major site for remnant removal is the space of Disse in the liver, where apo E directs binding to at least three different entities: the LDL receptor (53)(54)(55), the LRP (56), and HSPG (8,52,57). The LDL receptor accounts for more than half of remnant uptake (53), and it has a preference for particles smaller than 50 nm in diameter (58).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a separate chylomicron remnant receptor was suggested by observations that humans (5), rabbits (6), and mice (7) lacking the LDLR do not significantly accumulate chylomicron remnants in plasma. On the other hand, antibodies to the LDLR partially inhibit chylomicron remnant removal in mice (8), indicating an important physiologic role for the LDLR in remnant clearance. The LRP binds specifically to apo E, thus suggesting a role for the LRP in chylomicron remnant clearance (9).…”
Section: Introductionmentioning
confidence: 98%